Literature Study of Understanding the Physical Concepts of Straight Motion Materials Using the Gasing Method - Erwin Prasetyo; Budi Jatmiko; Adi Jufriansah (Indonesian Review of Physics (IRiP), 2020)
Not all physics concepts must be understood and mastered by deriving formulas through differential or integral techniques. Mechanics, for example, can be understood with simple logic without formulas, variables, and numbers. The fun method, or known as the GASING method, is a science learning method that has been offered by Yohanes Surya since 1996. This method offers fun learning activities for students. This research is a literature review of several books and research articles related to learning physics science using top methods. It turns out that with the spinning method, the concepts of velocity and acceleration in straight motion material can be understood easily and can solve some physics problems about straight motion without complicated physics formulas. All these physics problems are solved by simple logic and expressed in words.